1998
DOI: 10.1002/(sici)1097-0185(199810)252:2<215::aid-ar7>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural features of odontoclasts that resorb enamel in human deciduous teeth prior to shedding

Abstract: Three dental hard tissues, i.e., cementum, dentin, and enamel, are resorbed by multinucleated cells referred to as "odontoclasts." These cells have morphological and functional characteristics similar to those of bone-resorbing osteoclasts. However, concerning enamel resorption, which is a process that may occur during tooth eruption, satisfactory ultrastructural data on odontoclastic resorption are still lacking. Ultrastructural and histochemical characteristics of odontoclasts resorbing enamel of human decid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 62 publications
0
18
0
2
Order By: Relevance
“…Concerning ultrastructural features of odontoclasts resorbing enamel, it could be demonstrated that these tartrate-resistant acid phosphatase-positive multinucleated cells were quite similar to the cells resorbing dentine or cementum [13]. Rich in mitochondria, lysosomes and free polysomes, these cells secrete acids, organic components and hydrolytic enzymes performing phagocytosis of enamel crystals then to be found in large cytoplasmic vacuoles to be dissolved intra-cellularly.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning ultrastructural features of odontoclasts resorbing enamel, it could be demonstrated that these tartrate-resistant acid phosphatase-positive multinucleated cells were quite similar to the cells resorbing dentine or cementum [13]. Rich in mitochondria, lysosomes and free polysomes, these cells secrete acids, organic components and hydrolytic enzymes performing phagocytosis of enamel crystals then to be found in large cytoplasmic vacuoles to be dissolved intra-cellularly.…”
Section: Discussionmentioning
confidence: 99%
“…Domon et al (22) showed that in deciduous teeth undergoing resorption, the mean number of nuclei per odontoclast was 5.3, and only 2.9% of the resorbing cells were mononuclear. Comparative studies on cell ultrastructure have shown that odontoclasts resorbing dentin or cementum are similar to those resorbing enamel (23). Close similarity to bone osteoclasts was also documented.…”
Section: Cells Resorbing Hard Tissuesmentioning
confidence: 99%
“…Sahara et al (23) studied the resorption by odontoclasts of a superficial non-mineralized layer of predentin prior to the shedding of human deciduous teeth by light and electron microscopy. They found multinucleate cells on the predentin surface of the coronal dentine between the degenerated odontoblasts and resorption lacunae in the non-mineralized predentin.…”
Section: Etiology and Pathogenesis Of Internal Inflammatory Resorptionmentioning
confidence: 99%
“…After replantation of avulsed tooth, the most common complication is root resorption (1), as the result of the action of odontoclasts (9, 10). The morphological and functional characteristics of odontoclasts are similar to those of bone‐resorbing osteoclasts, with both odontoclasts and osteoclasts being differentiated from monocyte and macrophage lineage cells (11, 12). Increasing amount of evidence suggests that PDL cells closely resemble osteoblasts that can induce osteoclast‐like cell formation if co‐cultured with osteoclastic precursors, such as peripheral blood mononuclear cells (PBMC) (13, 14), mouse bone marrow cells (15, 16), and monocyte/macrophage lineage (RAW 264.7 cells) (17).…”
mentioning
confidence: 99%